Refinement and validation of a tool for stratifying patients with musculoskeletal pain. (3rd July 2021) - Dunn, Kate M.; Campbell, Paul; Lewis, Martyn; Hill, Jonathan C.; van der Windt, Danielle A.; Afolabi, Ebenezer; Protheroe, Joanne; Wathall, Simon; Jowett, Sue; Oppong, Raymond; Mallen, Christian D.; Hay, Elaine M.; et al.
Abstract: Background: Patients with musculoskeletal pain in different body sites share common prognostic factors. Using prognosis to stratify and treatment match can be clinically and cost‐effective. We aimed to refine and validate the Keele STarT MSK Tool for prognostic stratification of musculoskeletal pain patients. Methods: Tool refinement and validity was tested in a prospective cohort study, and external validity examined in a pilot cluster randomized controlled trial (RCT). Study population comprised 2, 414 adults visiting U.K. primary care with back, neck, knee, shoulder or multisite pain returning postal questionnaires (cohort: 1, 890 [40% response]; trial: 524). Cohort baseline questionnaires included a draft tool plus refinement items. Trial baseline questionnaires included the Keele STarT MSK Tool. Physical health (SF‐36 Physical Component Score [PCS]) and pain intensity were assessed at 2‐ and 6‐month cohort follow‐up; pain intensity was measured at 6‐month trial follow‐up. Results: The tool was refined by replacing (3), adding (3) and removing (2) items, resulting in a 10‐item tool. Model fit ( R 2 ) was 0.422 and 0.430 and discrimination ( c statistic) 0.839 and 0.822 for predicting 6‐month cohort PCS and pain (respectively). The tool classified 24.9% of cohort participants at low, 41.7% medium and 33.4% high risk, clearly discriminating between subgroups. The tool demonstrated model fit of 0.224 and discrimination 0.73 in trial participants. Multiple imputation confirmed robustness of findings. Conclusions: The Keele STarT MSK Tool demonstrates good validity and acceptable predictive performance and clearly identifies groups of musculoskeletal pain patients with different characteristics and prognosis. Using prognostic information for stratification and treatment matching may be clinically/cost‐effective. Significance: The paper presents the first musculoskeletal pain prognostic stratification tool specifically for use among all primary care patients with the five most common musculoskeletal pain presentations (back, neck, knee, shoulder or multisite pain). The Keele STarT MSK Tool identifies groups of musculoskeletal pain patients with clearly different characteristics and prognosis. Using this tool for stratification and treatment matching may be clinically and cost‐effective.